GENERATION Z’S PERSONAL FINANCIAL MANAGEMENT BEHAVIOUR: THE ROLE OF FINANCIAL TECHNOLOGY - Hidayati, Amalia Nuril; Wartisari, Wahyu Dwi; Oktafiani, Tiana; Melvin, M (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
This study is inspired by the declining quality of Generation Z's financial management behavior, most easily influenced by technological advancements and modernity. Along with advancements in financial technology, Generation Z prioritizes purchasing desirable products over assigning fixed or obligatory expenses. The goal of this study is to examine how financial technology affects Generation Z's financial management behavior, as modified by lifestyle characteristics and mediated by locus of control variables. This study's technique is quantitative. This study's population is Generation Z from Kedungwaru District, Tulungagung Regency. The sampling approach employed is disproportionate stratified random sampling (non-proportional stratified random sample), with the number of samples determined by the Slovin formula to get 116 research samples. Primary data was collected through the distribution of questionnaires. SEM-PLS is used to analyze technical data, including measurement and structural models. The findings revealed that financial technology has an influence on locus of control but has no effect on Generation Z's financial management behavior. Locus of control has the potential to mediate the impact of financial technology on Generation Z's financial management behavior. However, lifestyle moderating variables had little effect on the connection between financial technology variables and personal financial management behavior among Generation Z.